Analisis Pengaruh Modal Terhadap Petani Padi Sawah Di Kabupaten Bone Bolango - Bakari, Yuliana; Lusiana, Lusiana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rice farming is inseparable from the problem of capital and income obtained from farming results. This study aims to determine the availability of farming capital, farming income, and the effect of farming capital sources on rice farming income in Bone Bolango Regency. The study employs a quantitative research approach, utilizing non-probability sampling techniques and the accidental sampling method. The survey method is used for data collection. The analysis methods used are descriptive statistics, capital availability, and multiple linear regression. The results of the study showed that the average income of rice farmers in Bone Bolango Regency on an average land area of 1.4 ha is Rp4,627,350. Own capital and loan capital both contribute to farming capital, with the own capital having a positive and significant impact on rice farming income in Bone Bolango Regency, while the loan capital has a negative and significant impact.